Socially orientated digital storytelling among Saudi EFL learners: An analysis of its impact and content. Issue 2 (17th June 2019) - Al Khateeb, Ahmed A.
Abstract : Purpose: The current research presents a 14-week experience of developing socially orientated narratives in a digital mode, which involved 60 female Saudi English as a foreign language (EFL) learners. Initially working together, they were later divided into groups of approximately eight members each. The purpose of this research is to determine the benefits and challenges facing EFL leaners who are engaged with socially orientated digital-storytelling tasks. It also explores the nature of creating language-related socially orientated digital-storytelling projects and the main features associated with such projects. This practice targets the use of a new form of educational technologies that promotes educators' pedagogical strategies, as well as their social needs, by sharing learners' personal thoughts with others and cooperating and coordinating with other team members. Design/methodology/approach: The current research has been designed in line with qualitative analysis. A qualitative analysis approach was chosen as the study seeks to gain further understanding about the issue of socially orientated digital storytelling among EFL learners in Saudi Arabia. The two main research methods used for conducting this research were semi-structured interviews and analysis of the content produced by the participants. Both methods were selected to enable the participants to express their personal thoughts and feedback directly to the researcher. Findings: The findings have shown several benefits of this method, as well as highlighted the challenges regarding the application of such a practice in English language classes at university. The findings have indicated that such a novel educational atmosphere would result in the role of social orientation as a culture for enhancing learners' competence and willingness to share a co-learning experience being regarded more highly. In addition, the results have revealed how such group work can be constructed and the main aspects of content that exist in the digital stories produced. Research limitations/implications: One limitation of the current research is that it only included a group of female EFL students. Therefore, it is recommended that the same research be conducted on male EFL students in Saudi Arabia so that a comparative analysis can be made regarding the effects of socially orientated digital storytelling on both genders. In addition, it is recommended that the research be carried out among more classes containing female and male EFL students to be able to analyse the data quantitatively. Lastly, there remains the issue of convincing administrators, parents and instructors opposed to these ideas to implement this kind of project in formal language education, which is often independently orientated. Practical implications: The effect of such a practice is the improvements made to learners' academic and digital literacies. Specifically, students' academic-writing skills and abilities to tell stories are essential parts of this process that can be improved by learners during the online storytelling process. Originality/value: The research presents an application of a promising pedagogy that integrates digital technologies into different learning settings, including the context of learning English as a foreign language.